2012
DOI: 10.1111/faf.12010
|View full text |Cite
|
Sign up to set email alerts
|

Can fish really feel pain?

Abstract: We review studies claiming that fish feel pain and find deficiencies in the methods used for pain identification, particularly for distinguishing unconscious detection of injurious stimuli (nociception) from conscious pain. Results were also frequently misinterpreted and not replicable, so claims that fish feel pain remain unsubstantiated. Comparable problems exist in studies of invertebrates. In contrast, an extensive literature involving surgeries with fishes shows normal feeding and activity immediately or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
165
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(175 citation statements)
references
References 196 publications
1
165
0
9
Order By: Relevance
“…Although cartilaginous fish exhibit at least some pain-like behaviors, the fact that they do not have nociceptors is a defeater against attributions of pain experiences to them (Rose et al (2014); Smith and Lewin (2009);Snow et al (1993)). On the other hand, bony fish have nociceptors (Sneddon et al (2003)), which means that the absence of nociceptors cannot play the role of a defeater in this case 1 .…”
Section: The No Cortex No Cry Argumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cartilaginous fish exhibit at least some pain-like behaviors, the fact that they do not have nociceptors is a defeater against attributions of pain experiences to them (Rose et al (2014); Smith and Lewin (2009);Snow et al (1993)). On the other hand, bony fish have nociceptors (Sneddon et al (2003)), which means that the absence of nociceptors cannot play the role of a defeater in this case 1 .…”
Section: The No Cortex No Cry Argumentmentioning
confidence: 99%
“…Although few would doubt that most mammals are conscious, debates revolve around the possibility of fish, cephalopods, crustaceans or insects being conscious, and more specifically, feeling pain (Allen (2004); Edelman et al (2005); Edelman and Seth (2009);Elwood (2012); Godfrey-Smith (2017); Griffin (1976); Tye (2017)). The most central debate features proponents of consciousness in animals such as fish (Braithwaite (2010); Huntingford et al (2006); Jones (2013); Sneddon (2011)) and insects (Barron and Klein (2016)) versus opponents to the existence of consciousness in those animals (Derbyshire (2016); Rose (2007); Rose et al (2014); Key (2015Key ( , 2016; Key et al (2016)). …”
Section: Introductionmentioning
confidence: 99%
“…C fibres in mammals contribute to dull, 'thudding' pain whereas the faster conducting A-delta fibres are believed to signal 'first' pain to the CNS. Sceptics have suggested that the small number of C fibres means fish do not experience pain (Rose et al, 2014). Given the differences in lifestyle, morphology and so on, fish neuroanatomy is not identical to the human system; however, A-delta fibres conduct at a faster speed, so perhaps the fish system is more rapid and efficient.…”
Section: Pain In Fishmentioning
confidence: 99%
“…In humans, negative 'feelings' of discomfort or suffering are experienced alongside the injury and this is termed pain. The concept of pain occurring in animals has been extensively debated, with some authors suggesting only primates and humans can experience the adverse affective component as they possess a human (or similar in primates) neocortex (Rose, 2002;Rose et al, 2014). Opposing this opinion, scientists suggest that the negative experience that accompanies tissue damage is crucial in altering an animal's subsequent behaviour to perform protective and guarding reactions, enabling the animal to avoid such stimuli in future, and for avoidance learning to occur (Sneddon et al, 2014).…”
mentioning
confidence: 99%
“…On the other hand, in the scientific literature there is debate about the ability of fish to experience pain and suffering (Braithwaite and Ebbesson, 2014), as some authors (Rose et al, 2014) still contest the capacity of fish for mental awareness due to the absence of neocortex. The third main reason is connected with the fact that even similar fish species may exhibit considerable physiological and/or behavioral differences (Daskalova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%